STRATEGI SOFT POWER DALAM EKSPANSI EKONOMI CHINA DI TIMUR TENGAH: STUDI KASUS KERJASAMA CHINA-IRAN - R. Muhammad Teguh Nurhasan Affandi, Dina Yulianti (Fakultas Ilmu Sosial Ilmu Politik Pr, 2018)
The unilateral United States withdrawal from JCPOA in May 2018 and US efforts to embargo Iran, according to some observers, have provided opportunities for China to enlarge its economic dominance in the Middle East. Previously, China have actively established strong economic relations with most of Middle Eastern countries. This phenomenon raises research questions, what is the key to China's success in carrying out economic expansion in the Middle East in the midst of various conflicts in the region? The authors focuses the research on China's soft power strategy which is assumed to have a big role in the success of the country's economic and trade cooperation in the region, especially in the case of China-Iran cooperation. Through reviewing literature and mass media news, this study found a new dimension in China's soft power strategy towards Iran, namely the very strong role of 'value', including the value of loyalty, refusal towards radicalism and terrorism, and resistance to US domination.